Magnetogels: Prospects and Main Challenges in Biomedical Applications - Sérgio R. S. Veloso; Paula M. T. Ferreira; J. A. Martins; Paulo J. G. Coutinho; Elisabete M. S. Castanheira (MDPI AG, 2018)
Drug delivery nanosystems have been thriving in recent years as a promising application in therapeutics, seeking to solve the lack of specificity of conventional chemotherapy targeting and add further features such as enhanced magnetic resonance imaging, biosensing and hyperthermia. The combination of magnetic nanoparticles and hydrogels introduces a new generation of nanosystems, the magnetogels, which combine the advantages of both nanomaterials, apart from showing interesting properties unobtainable when both systems are separated. The presence of magnetic nanoparticles allows the control and targeting of the nanosystem to a specific location by an externally applied magnetic field gradient. Moreover, the application of an alternating magnetic field (AMF) not only allows therapy through hyperthermia, but also enhances drug delivery and chemotherapeutic desired effects, which combined with the hydrogel specificity, confer a high therapeutic efficiency. Therefore, the present review summarizes the magnetogels properties and critically discusses their current and recent biomedical applications, apart from an outlook on future goals and perspectives.